Ancestral landscapes in human evolution culture, childrearing and social wellbeing - Narváez, Darcia; Valentino, Kristin; Fuentes, Agustin; McKenna, James J.; Gray, Peter (Oxford University Press, 2014)
This title addresses how a shift in the way we parent can influence child outcomes. It examines evolved contexts for mammalian development, optimal and suboptimal contexts for human evolved needs, and the effects on children's development and human wellbeing.